Introduction to lipidomics : from bacteria to man - Leray, Claude (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
'The first comprehensive book on lipidomics, this long-awaited work inventories the huge variety of lipid molecules present in all aspects of life. It uses sensitive analytical techniques, such as mass spectrometry, to characterize structures and simplify the association of names with their appropriate structures. Fulfilling the spirit of inclusiveness, it details structures from marine ecosystems, little known structures from bibliographic data, cultural references and context, biological functions, and possible pharmacological properties. The text is highly informative and educational while simultaneously being anecdotal and interesting to read'--
'Preface Classification Since the origins of organic chemistry, lipids or fats were reduced to a mixture of solid greases (or tallow) and fluid oils (concept of H. Braconnot, 1815), but it was M.E. Chevreul who proposed in 1823 the first logical classification. Thus, he classified all lipids known at that time in two divisions and six kinds based on a physical property (distillation) and on a chemical property (saponification) as well as on the nature of the components of these lipids. Beside oils, greases, tallow, and waxes, Chevreul included in the concept of fat, the resins, the balsams, and volatile oils (or essential oils). One can thus say that in the light of the current data, the classification of the lipids by Chevreul is the model of that still accepted almost two centuries later. Although phosphorylated lipids were discovered in the mammalian brain and the hen egg in 1847 by the French chemist T.N. Gobley, for approximately a century after, chemists regarded lipids ('fats') as only the simple lipids made of fatty acids and glycerol. American chemists quickly integrated the discovery of many phospholipids and glycolipids by the German physician J.L. Thudichum (1874-1884) and proposed by 1920 a unified classification of'lipoids' distributed in three groups the simple lipoids (greases and waxes), the complex lipoids (phospholipids and glycolipids), and the parent lipoids (fatty acids, alcohols, sterols). In 1923, French chemist G. Bertrand provided the foundations of a new nomenclature in biological chemistry and proposed the term'lipides,' including not only the traditional fats (glycerides) but also the'lipoids,' molecules with'complex constitution,' such as cholesterol esters or the cerebrosides'--
Pembekal: Areesh Education & Trading, Tel: 03-7842 6036
Includes bibliographical references and index.
Translated from French.
Keywords: Lipids -- classification; Lipids -- Analysis; Lipids -- physiology; MEDICAL -- Biochemistry; SCIENCE -- Chemistry -- Organic; TECHNOLOGY & ENGINEERING -- Food Science; Lipids; Classification